DETEKSI MASKER WAJAH SECARA REALTIME DENGAN ARDUINO UNTUK MENCEGAH PENYEBARAN COVID-19 - Arafat arafat; Silvia Ratna; Wagino Wagino (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The emergence of the COVID-19 pandemic has had a lasting impact on countries around the world since 2019. Face mask detection has been a significant advance in the field of image processing and deep learning studies. Many face detection models have been designed using different algorithms and techniques. The approach proposed in this proposal is developed to prevent people without masks from entering public places (i.e. Malls, Universities, Offices, …etc) by detecting face masks using deep learning, TensorFlow, Keras, and OpenCV methods and sending a signal to the connected Arduino device. to the door to be opened. To detect a person's face in real-time and identify whether the person is wearing a mask or not. This method uses datasets collected from various sources.